Internal Lifshitz tails for discrete Schrödinger operators - Hatem Najar (International Journal of Mathematics and Mathematical Sciences)
We consider random Schrödinger operators Hω acting on l2(ℤd). We adapt the technique of the periodic approximations used in (2003) for the present model to prove that the integrated density of states of Hω has a Lifshitz behavior at the edges of internal spectral gaps if and only if the integrated density of states of a well-chosen periodic operator is nondegenerate at the same edges. A possible application of the result to get Anderson localization is given.